What's Behind the Recent Rise in Profitablity? - Edward N. Wolff (Levy Economics Institute of Bard College, 2000)
Profitability in the United States has been rising since the early 1980s and by 1997 was at its highest level since its postwar peak in the mid 1960s, and the profit share, by one definition, was at its highest point. In this paper I examine the role of the change in the profit share and capital intensity, as well as structural change, on movements in the rate of profit between 1947 and 1997. Its recent recovery is traced to a rise in the profit share in national income, a slowdown in capital-labor growth on the industry level, and employment shifts to relatively labor-intensive industries.
Keywords: 330